2 industries receive UMP Excellence Awards - Siti Nurfarmy, Ibrahim (2020)
Kuantan, 28 August 2020 – BASF Petronas Chemical Sdn. Bhd. (BASF) and Volkswagen Group Malaysia (VGM) were named the recipients of the Best Industry Partner Award in Majlis Apresiasi in conjunction with the Innovation & Quality Day of Universiti Malaysia Pahang (UMP) 2020 at the Sports Complex, UMP Gambang recently.